The Evolution of Constitutionalism in the Netherlands: A Critical Analysis of Institutional Reforms - Johannes de Vries; Marieke van Dijk; Johanna Elisabeth van Dalen; Wilhelmus Hendrikus de Groot; Frederik Antonius van Leeuwen; Pieter Johannes de Jong (Journal of Multidisciplinary Law Studies, 2026)
This article examines the evolution of constitutionalism in the Netherlands through a critical analysis of institutional reforms that have shaped its contemporary legal order. Traditionally characterized by a strong emphasis on parliamentary sovereignty and a limited role for constitutional review, the Dutch constitutional framework has undergone gradual institutional adaptation through the expansion of judicial oversight, administrative accountability mechanisms, and the incorporation of European human rights norms in response to growing demands for transparency, accountability, and the protection of fundamental rights. This study employs a normative juridical and historical-institutional approach to evaluate how institutional reforms reshape the balance between parliamentary sovereignty and constitutional accountabilityto explore key reforms, including the strengthening of judicial oversight, the influence of international and European legal norms, and the increasing role of independent oversight bodies. The findings indicate an incremental redistribution of constitutional authority from purely political institutions toward judicial and oversight mechanisms, where the principles of the rule of law and checks and balances are increasingly emphasized. However, tensions persist between traditional doctrines and emerging constitutional practices, particularly in the context of democratic legitimacy and judicial activism. This article argues that the evolution of constitutionalism in the Netherlands reflects a dynamic interplay between legal continuity and institutional change, offering a comparative perspective on how constitutional systems adapt to increasing demands for accountability, rights protection, and supranational legal integration